The Path of Military Power Interference in the Politics of Thailand - Septyanto Galan Prakoso (Global South Review, 2014)
Military element is undoubtedly important in order to protect a country's sovereignty. However, sometimes the functional aspect of military power can be biased, as military personnel also included in the political affairs. In some country this phenomenon happened, when military element through its personnel can become a part of government/bureaucratic mechanism. Tension is possible to rise between civil and military itself. In Thailand, military power can meddle in the country's politics through coup, even though it only runs the role to observe at first. The coup has happened for years in Thailand's modern history, noticeably started since 1932 after the revolution. Since then, military power always able to interfere Thailand’s political affairs and cause the fall and change of the government. Recently, the same things happened in May 7th, 2014 when Thai military launched a coup towards Prime Minister Yingluck Shinawatra's government, and ended her spell as prime minister since August 5th, 2011. Therefore, in order to deeply explore Thailand's military's activity in meddling inside the politics, this journal will try to trackback through Thailand's history and discover the reasons and factors which influenced military power's interference in Thailand politics.